Application of Lambda Architecture in the Intelligent Operation and Maintenance System for Rail Transit Vehicles - HU Weimin (Kongzhi Yu Xinxi Jishu)
In view of the massive on-board data processing requirements in the intelligent operation and maintenance system for rail transit vehicles, this paper proposes a data processing architecture scheme based on the principle of Lambda architecture in order to overcome the performance bottlenecks in the reception, processing, storage, query, analysis and other links of massive data under the single-point data processing mode. It adopts distributed server cluster as the underlying hardware support and uses distributed processing framework, which greatly improves data concurrent processing ability of the operation and maintenance system. Experimental results show that compared with the single point data processing mode, processing performances are greatly improved in every link by this scheme. The application of many railway intelligent operation and maintenance projects also proves that the rail intelligent operation and maintenance system based on this scheme can effectively meet the demand of rapid processing of massive data issued by vehicles.